In Search of Singularity Poetry in Poland and China Since 1989 - Krenz, Joanna (Brill, 2022)
In Search of Singularity introduces a new "compairative" methodology that seeks to understand how the interplay of paired texts creates meaning in new, transcultural contexts. Bringing the worlds of contemporary Polish and Chinese poetry since 1989 into conversation with one another, Joanna Krenz applies the concept of singularity to draw out resonances and intersections between these two discourses and shows how they have responded to intertwined historical and political trajectories and a new reality beyond the human. Drawing on developments such as AI poetry and ecopoetry, Krenz makes the case for a fresh approach to comparative poetry studies that takes into account new forms of poetic expression and probes into alternative grammars of understanding.